CNS / CSCN Platform Presentations: The potential influence of abnormal blood platelet count on mortality, impairment and disability after acute ischemic stroke. (3rd June 2015) - Furlan, JC; Fang, J; Silver, FL
Abstract : Background: We hypothesized that abnormal blood platelet count (BPC) is associated with poorer outcomes after acute ischemic stroke. Methods: We included data from the Registry of the Canadian Stroke Network on consecutive patients with acute ischemic stroke admitted between July/2003 and March/2008. Patients were divided into groups as follows: low BPC (<150, 000/mm3), normal BPC (150, 000 to 450, 000/mm3) and high BPC (>450, 000/mm3). Primary outcome measures were the frequency of moderate/severe strokes on admission (Canadian Neurological Scale: <8), greater degree of disability at discharge (modified Rankin score: 3-6), and 30-day and 90-day mortality. Results: We included 9, 230 patients. Both low and high BPC were associated with higher 30-day mortality (p=0.0103) and 90-day mortality (p=0.0189) following acute ischemic stroke. The Kaplan-Meier curves indicate that abnormal BPC is associated with greater mortality after acute ischemic stroke (p=0.0002). Nonetheless, abnormal BPC was not associated with degree of impairment (p=0.3734), degree of disability (p=0.684), or length of stay (LOS) in the acute stroke care center (p=0.9541) after adjustment for major potential confounders. Conclusions: In patients with acute ischemic stroke, thrombocytopenia and thrombocytosis on the initial admission is associated with higher mortality after stroke. Abnormal BPC does not adversely affect the degree of impairment and disability, or LOS in the acute care center after acute ischemic stroke.